Peran Ganda Wanita Karir Dalam Manajemen Keluarga - Maulidyah Amalina Rizqi; Subhan Adi Santoso (Jurnal Manajerial, 2022)
Background – Rapid economic development and growth has encouraged women to participate in fulfilling household needs. So it is not surprising that nowadays we often find working women. Women who have a career when they are married will have a dual role, and this will have an impact on family management. Aim – This study aims to see the dual role of career women in carrying out family management. Design / methodology / approach – The research method used is descriptive qualitative, with interview and observation data collection techniques. Findings – The results of this study state that every woman who has multiple roles must be able to manage their lives well and divide it into four management types, namely time management, conflict management, self management and education management. If career women can manage these four managements well, their family life and career will be ideally organized. Research implication – The results of this study provide knowledge to the reader to be able to manage the organization in the family, especially for families who have multiple roles. Limitations – The focus of this study is only on women who live in urban areas.